Real-world Effectiveness of Ledipasvir/Sofosbuvir (LDV/SOF) for 8 weeks in Patients Coinfected with HCV and HIV-1. (4th October 2017) - Ruane, Peter; Buggisch, Peter; Moreno, ANA; Isakov, Vasily; Backus, Lisa; Ain, Dani; Gonzalez-Garcia, Juan; Naik, Sarjita; Mehta, Swarup; Lee, Jina; Llewellyn, Joe; Mertens, Michael; et al.
Abstract: Background: Real world cohorts (RWC) have demonstrated excellent efficacy of LDV/SOF for 8 weeks in HCV monoinfected patients. Real world effectiveness data of LDV/SOF for 8 weeks in HIV/HCV coinfection is emerging from several multiple single-center and multicenter prospective and retrospective cohorts. The aim of this study was to describe the effectiveness of the single tablet regimen of LDV/SOF for 8 weeks in HCV genotype (GT) 1 patients with HIV/HCV coinfection in RWC. Methods: In this descriptive analysis, data from two prospective studies, one investigator sponsored and 1 registrational trial, one prospective RWC, three retrospective RWC of LDV/SOF for 8 weeks in HIV/HCV co-infected patients were compared. RWC were selected based on willingness to participate and had at least 15 HIV/HCV co-infected patients. The prospective trials include data from Ain et al (investigator sponsored) and Isakov et al (registrational trial). The RWC include the Deutsches Hepatitis C-Register, Madrid Coinfection Registry (Madrid-CoRe), Veterans Affairs HCV Registry, and Slim et al, representing diverse patient populations from Europe and US. Baseline characteristics and efficacy were analyzed. Results: The majority of the 294 patients included in this descriptive analysis were GT 1, treatment naïve (TN), noncirrhotic (NC), and had a HCV viral load < 6 million. The prospective cohorts enrolled 79 patients with the following baseline characteristics: mean age (43 years), male (66%), white (89%), and GT 1a (41%). The RWC studies assessed enrolled 215 patients with the following overall baseline characteristics: mean age (54 years) male (84%), white (82%), and GT 1a (75%) in those that reported demographics. The overall SVR12 from six diverse real world and post-marketing cohorts was 94% (277/294). The individual study results are presented in Table 1. Conclusion: This analysis of diverse cohorts from the EU and US yielded high SVR rates similar to SVR rates seen in multiple RW monoinfected cohorts and supports the use of 8 weeks of LDV/SOF in TN, NC GT 1 HIV/HCV coinfected patients with a baseline HCV viral load < 6 million. Disclosures: P. Ruane, Gilead: Investigator, Scientific Advisor and Shareholder, Consulting fee and Research support; Merck: Speaker's Bureau, Speaker honorarium; Boehringer: Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; Janssen: Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; Abbott: Investigator, Scientific Advisor and Speaker's Bureau, Research support and Speaker honorarium; Idenix: Investigator, Research support; ViiV: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; BMS: Consultant, Investigator and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; P. Buggisch, Janssen: Scientific Advisor, Consulting fee; Abbvie: Scientific Advisor, Consulting fee; BMS: Scientific Advisor, Consulting fee; Falk: Speaker's Bureau, Speaker honorarium; MSD: Speaker's Bureau, Speaker honorarium; Gilead: Speaker's Bureau, Speaker honorarium; Merz: Speaker's Bureau, Speaker honorarium; V. Isakov, BMS: Speaker's Bureau, Speaker honorarium; Abbvie: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; Gilead: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; Merck: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; Janssen: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; R-Pharm: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; J. Gonzalez-Garcia, Gilead: Board Member and Speaker's Bureau, Speaker honorarium; MSD: Speaker's Bureau, Speaker honorarium; Abbvie: Board Member and Speaker's Bureau, Speaker honorarium; Janssen: Board Member and Speaker's Bureau, Speaker honorarium; Ciliag: Speaker's Bureau, Speaker honorarium; BMS: Board Member and Speaker's Bureau, Speaker honorarium; S. Naik, Gilead Sciences: Employee, Salary; S. Mehta, Gilead Sciences: Employee, Salary; J. Lee, Gilead Sciences: Employee, Salary; J. Llewellyn, Gilead Sciences: Employee, Salary; M. Mertens, Gilead Sciences: Employee, Salary; M. Natha, Gilead Sciences: Employee, Salary; A. Osinusi, Gilead Sciences: Employee, Salary; J. Slim, Gilead: CME/CE, Consultant, Investigator and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; Abbvie: CME/CE, Consultant and Investigator, Consulting fee, Research support and Speaker honorarium; Merck: CME/CE, Consultant and Investigator, Consulting fee, Research support and Speaker honorarium; ViiV: CME/CE, Consultant and Investigator, Consulting fee, Research support and Speaker honorarium; Janssen: CME/CE and Consultant, Consulting fee and Speaker honorarium; BMS: CME/CE, Speaker honorarium; K. Zhdanov, MSD: Speaker's Bureau, Speaker honorarium; Novartis: Speaker's Bureau, Speaker honorarium; Roche: Speaker's Bureau, Speaker honorarium; Biocad: Speaker's Bureau, Speaker honorarium; BMS: Consultant, Consulting fee; Abbvie: Investigator, Research support; Gilead: Investigator, Research support; R-Pharm: Investigator, Research support; Janssen: Scientific Advisor, Consulting fee; S. Zeuzem, Abbvie: Consultant, Consulting fee; Gilead: Consultant, Consulting fee; Merck: Consultant, Consulting fee; BMS: Consultant, Consulting fee; Janssen: Consultant, Consulting fee